Simulation of Linear Feedback Control of D-Statcom for Voltage Sag Mitigation - Zulkifli, Shamsul Aizam (2006)
Recently, the demands of electrical supply by industries and domestics customers have increased tremendously. This is due to the increase of large loads which are sensitive in industries like semiconductor and the building of new housing estates. These have caused power quality problems to both end users by the increasing demand of electricity. The major power quality problems that always occur in power systems are voltage sag, unbalanced voltage and unbalanced current. Various circuit topologies and controls have been developed, aimed at mitigating these power quality problems. One of the solutions is by using the Custom Power devices. These Custom Power devices respond to poor power quality problems such as voltage sag, unbalanced voltage and unbalanced current by improve the quality of the system. Custom Power family consists of Distribution Static Compensator (D-STATCOM), Dynamic Voltage Restorer (DVR), Solid State Fault Current Limiter (SSFCL), Active Power Filter (APF), and Solid State Transfer Switch (SSTC) are power electronic based devices. These Custom Power devices will solve power quality problems at the distribution system by injecting voltage or current referring to the amount of reference voltage or current fiom the distribution system. In this thesis, D-STATCOM has been used as a device to solve voltage sags and unbalanced fault conditions. From the studies, the conventional D-STATCOM controller that uses Proportional Integration (PI) controller is capable of solving voltage sag but not capable of solving the unbalanced conditions. This is because the conventional PI controller cannot respond to the negative sequence components. The negative sequence component is induced by unbalanced faults which happen in a system. This negative sequence component will block the Gate Turn Off (GTO) Thyristor fiom firing. From the studies, there are two types of techniques in solving negative sequence components namely negative sequence controller or using DQ transformation of the current. This thesis explains the application of DQ transformation which changes the 3 phase components to direct and quadrate components and the pole placement controller. Both of these techniques have been consider for designing the new type of controller. This new type of controller is capable of giving order to D-STATCOM to inject the current to solve voltage sag and unbalanced conditions. The simulations of the DSTATCOM and the pole placement controller were implemented in Mathematical Laboratory (MATLAB) program version 6.5 developed by MATHWORKS Inc. The D-STATCOM has been connected to the 1 lkV distribution system in shunt with fault components. The results obtained from the simulations clearly showed that the designed D-STATCOM with the new pole placement controller is capable of mitigating voltage sag and unbalanced fault conditions. The developed simulation model will be useful for future power quality studies in distribution systems.